(untitled) (Indian Journal of Arid Horticulture, 2025)
Anthurium are tropical plants grown for their showy cut flowers and attractive foliage. These tropical cut flowers received a boost with the emergence of anthurium in the world scenario, dominated largely by sub-tropical and temperate cut flowers. Because of its long shelf life, anthurium is an excellent export product. The flowers are perishable and therefore need to be treated with suitable chemicals to enhance their life in vase and to improve the quality. One important factor causing senescence is the increase in loss of water from flower parts coupled with the reduced rate of water uptake during storage. Various holding solutions preservatives are used for the long term storage of anthurium cut flowers.